Zinc-Nucleated D2 and H2 Crystal Formation from Their Liquids. (1st September 2016) - Bernat, T. P.; Petta, N.; Kozioziemski, B.; Shin, S. J.; Harding, D. R.
Abstract: Calorimetric measurements at University of Rochester Laboratory for Laser Energetics of D2 crystallization from the melt indicate that zinc can act as a heterogeneous nucleation seed with suppressed supercooling. We further studied this effect for a variety of zinc substrates using the optical-access cryogenic sample cell at Lawrence Livermore National Laboratory. Small supercoolings are observed, some as low as 5 mK, but results depend on the zinc history and sample preparation. In general, thin samples prepared by physical vapor deposition were not effective in nucleating crystal formation. Larger (several-millimeter) granules showed greater supercooling suppression, depending on surface modification and granule size. Surfaces of these granules are morphologically varied and not uniform. Scanning electron microscope images were not able to correlate any particular surface feature with enhanced nucleation. Application of classical nucleation theory to the observed variation of supercooling level with granule size is consistent with nucleation features with sizes <100 nm and with wetting angles of a few degrees.